Bridging knowledge and practice gaps in pharmacovigilance: a study among medical interns in Uttar Pradesh - Dwivedi, Aanchal; Mishra, Aishwarya; Sharma, Kartikey (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Adverse drug reactions (ADRs) are a major public health concern globally, contributing to significant morbidity and mortality. Despite the presence of pharmacovigilance systems, underreporting is common within medical colleges and antimicrobial stewardship programs, particularly in India. Medical interns are pivotal in ADR reporting, but gaps persist between their knowledge and practical application. By integrating pharmacovigilance into medical curricula, healthcare professionals can be better equipped to identify and report ADRs, ultimately enhancing patient outcomes. This study aims to evaluate the knowledge, attitudes, and practices (KAP) of ADR reporting among medical interns at Sarojini Naidu Medical College, Agra, and identify barriers to reporting. Methods: A cross-sectional study was conducted among 125 medical interns using a pre-tested, structured questionnaire to assess their KAP regarding ADR reporting. Data were analyzed using descriptive statistics in Microsoft Excel. Results: While 95% of interns were aware of ADRs and 70% understood the need to report them, only 25% had reported an ADR. Barriers included time constraints, lack of training, and legal concerns. Conclusion: The study highlights high awareness but low reporting rates among medical interns, emphasizing the need for targeted educational interventions and streamlined reporting systems to improve pharmacovigilance practices.